Pengembangan Aplikasi Pelayanan Administrasi Kependudukan Desa berbasis Mobile Web (Studi Kasus: Kantor Desa Wonodadi) - Alfin Zaenal Kamala; Agi Putra Kharisma; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Correspondence service is one of the important activities in every village. One of the administrative services that are routinely directly related to the community is village population administration services such as making domicile letters, moving certificates, death certificates, application letters for making identity cards and other population service letters. correspondence service at the Wonodadi village office, Wonodadi sub-district, Blitar district. In its implementation it is only handled by an administrative apparatus, so it is not uncommon for the process of making letters to be quite time consuming. Registered letters are only manually archived using a notebook, often having an impact on the process of making routine administrative reports which are sometimes inappropriate due to recording errors such as forgetting to record or being recorded more than once. Therefore, in this study the authors built an application for village population administration services. The platform used to develop this application is responsive web-based, because the majority of Wonodadi villagers have smartphones to access the internet. The development method used to create applications is the prototyping method. This method supports fast and flexible development by utilizing the evaluation process to determine factors that can affect the development process. Based on the results of the analysis there are 12 functional requirements and 2 non-functional requirements. In testing the functional requirements using the blackbox testing method, the results are 100% valid. The compatibility test uses a scenario by running the application on several smartphone and desktop mobile devices using a browser that produces a compatibility value of 100% that can be run. Meanwhile, the usability test was tested using the usability scale method with an average result of 81 points for the villagers and 82 points for the village government.